Looking at Seven Years of Published Research Through a Bibliometric Lens (JSEAHR in Focus) - Firmansyah, Firmansyah; Sauki, Muhammad; Hidayat, Rahmad (Universitas Sultan Ageng Tirtayasa, 2025)
This bibliometric review used Excel spreadsheet tabulations and the VOSviewer software to analyze 92 research articles from 2017 to 2023 to discover productivity patterns, collaboration networks, and research trends in JSEAHR. The findings show a fluctuating production pattern of JSEAHR's annual publications, reflecting the dynamics of contributions by human rights researchers in Southeast Asia. Examination of authorship patterns highlighted individual researcher dedication and collaborative efforts, with 51 single and 41 multi-author articles. The geographic distribution of authors involves 23 countries, and Indonesia emerges as the central contributor with 76 authors. The institutional affiliation analysis highlights the diversity of contributors from leading higher education institutions in various countries as well as government and non-government institutions. Exploration also detected a diversity of research methodologies, with conceptual-normative and juridical-sociological approaches as dominant. The Scopus database confirms the citation influence of JSEAHR, with 71 indexed pieces of literature, 38 of which have citation data. Various global journals across disciplines reference this journal, contributing to its increasingly widespread impact. Relevant to future research directions, there are potential areas that researchers could hope in on further, such as transitional justice, disability rights, and environmental rights. In conclusion, this bibliometric analysis positions JSEAHR as a significant platform for diverse and impactful research on human rights issues. To ensure the continued influence of this journal in shaping a comprehensive global narrative on human rights in the post-COVID-19 era, it is crucial to maintain its collaborative and interdisciplinary spirit as it navigates an evolving landscape.